2013
DOI: 10.1021/ol402568j
|View full text |Cite
|
Sign up to set email alerts
|

A β-Peptide Agonist of the GLP-1 Receptor, a Class B GPCR

Abstract: Previous work has shown that certain β3-peptides can effectively mimic the side chain display of an α-helix and inhibit interactions between proteins, both in vitro and in cultured cells. Here we describe a β3-peptide analog of GLP-1, CC-3Act, that interacts with the GLP-1R extracellular domain (nGLP-1R) in vitro in a manner that competes with exendin-4 and induces GLP-1R-dependent cAMP signaling in cultured CHO-K1 cells expressing GLP-1R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 50 publications
0
46
0
Order By: Relevance
“…Introduction of just one or two α➔β replacements in the central portion of a PTHR1 agonist peptide can substantially diminish receptor activation potency, 2830 which shows that proper selection of substitution sites in peptide hormone mimics is crucial. 30 In a study of 19-mer peptides that adopt a specific but irregular conformation and bind to vascular endothelial growth factor (VEGF), we found that it was not possible to introduce α➔β replacements without diminution of affinity for VEGF. 31 Therefore, whether α/β segments can serve as functional mimics of non-helical or conformationally uncharacterized α-peptide segments remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of just one or two α➔β replacements in the central portion of a PTHR1 agonist peptide can substantially diminish receptor activation potency, 2830 which shows that proper selection of substitution sites in peptide hormone mimics is crucial. 30 In a study of 19-mer peptides that adopt a specific but irregular conformation and bind to vascular endothelial growth factor (VEGF), we found that it was not possible to introduce α➔β replacements without diminution of affinity for VEGF. 31 Therefore, whether α/β segments can serve as functional mimics of non-helical or conformationally uncharacterized α-peptide segments remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, PTH analogs containing one to three β-residue replacements were used to probe local conformational requirements, and many of these replacements caused profound declines in agonist activity 9,10 . The peptide hormone GLP-1(7-37), which activates a different B-family G protein–coupled receptor, parallels PTH(1-34) in that the C-terminal portion is α-helical when bound to the receptor 11 ; recent efforts to replace the α-helix with a purely β-residue segment essentially abolished activity 12 . In contrast, we show that proper choice of β-residue identity and location allows α→β residue replacement at up to seven distributed sites with maintenance of PTH(1-34)-like potency, but alteration of the pharmacokinetic profile.…”
mentioning
confidence: 99%
“…14). Alternative strategies for introducing α→β replacements in peptide hormones have been largely unsuccessful in terms of retaining native potency 9,10,12 . α/β-peptides A5-D5 were easily prepared by conventional solid-phase synthesis.…”
mentioning
confidence: 99%
“…A long α-helix formed in the C-terminal portion of exenatide makes extensive contacts with the extracellular domain of GLP-1R [47]. Replacement of this α-helix-forming segment with a β-peptide segment caused a dramatic loss in agonist potency [48]. …”
Section: β-Peptidesmentioning
confidence: 99%